Peningkatan Hasil Belajar Siswa Kelas IV Pada Materi Perkalian Berbantuan Media Pembelajaran PAPINKA Dengan Model Pembelajaran Kooperatif Make A Match - Mila Muhimmatul Alwiyyah; Nunik Tri Ayuni Kumalasari; Diana Ermawati (LPPM Universitas Buana Perjungan Karawang, 2024)
This research is motivated by the world of education which requires innovation in learning media to be more creative and not boring. This study aims to determine the increase in learning outcomes of students in class IV SD 1 Dersalam which totaled 26 students through the application of the Make A Match type cooperative learning model assisted by PAPINKA learning media. This type of research is Classroom Action Research (CAR). Before applying the Cooperative learning model of the Make A Match type assisted by PAPINKA learning media, the class average score in the cognitive domain was 46.3, the percentage of completeness was 15.3%. In cycle I, the learning outcomes of students were the class average in the cognitive domain of 77.6 with a completeness percentage of 69%. In cycle II, the learning outcomes of students were the class average in the cognitive domain of 93 with a completeness percentage of 100%. Based on the results of the research and discussion, as well as the analysis of the data that has been described, it can be concluded that cooperative learning of the Make A Match type assisted by PAPINKA learning media can improve learning outcomes in cognitive aspects or knowledge of Mathematics in class IV SD 1 Dersalam academic year 2022/2023.